A Meta-Analysis of The Effect Teams Games Tournament (TGT) in Biology Learning Toward Student Learning Outcomes - Halimatussya’diyah Hasibuan; Jeneri Puspita Sari Br Lingga; Siti Nurbaya; Olivia Erza Thania; Nurul Azmi Ramadhani; Windi Arningsi Nainggolan (Journal of Biology Learning, 2022)
Learning is a complex process which contains several aspects. These aspects are an increase in the amount of knowledge, the ability to remember and reproduce, there is an application of knowledge, inferring meaning, interpreting and relating to reality, and a change as a person. This research is hoped that  can give contribute for schools, teachers, and students. This researcher has led a review entitled Meta-examination of the impact of the Teams Games Tournament (TGT) learning model on science subjects on student learning outcomes using the connection test technique the Team Games Tournament (TGT) Learning Model on Student Learning Outcomes in Science Learning.  is a scalable method for consolidating the consequences of at least two comparable examinations to obtain a mix of quantitative information. This research plans to determine student learning outcomes in science learning after the Team Games Tournament (TGT) learning model is applied.  This research is uses the strategy of Meta Correlation Analysis which is an attempt to summarize various exploratory results quantitatively based on the consequences of important investigations. In this research is can find that there is an impact from the use of the learning model the fun type is Teams Games Tournament Tournament assisted by general media on student learning outcomes. Utilization of Cooperative Learning Model Types of Teams Games Tournament Assisted by Audio Visual has an impact on student learning outcomes. Likewise, TGT can also train self-confidence and all students are given the opportunity to attend classes effectively. Opening the door for students to be interested can make students more dynamic and increase their knowledge.